Analisis Pengaruh Pembayaran Pajak Melalui Aplikasi Signal, Pembayaran Online Lainnya, dan Layanan Night Drivethru Terhadap Penerimaan Pajak Kendaraan Bermotor di KPPD Kabupaten Sleman - Rizka Angga Nuary; Sulastiningsih (Masyarakat Ekonomi Syariah Bogor, 2025)
The Sleman Regency KPPD offers many types of services to the community in order to maximize tax revenue. There are three types of services that are interesting to study. The first is the SIGNAL application, which is an official digital application developed in collaboration with the Indonesian National Police Traffic Corps that provides online vehicle tax (PKB) payments and annual vehicle registration (STNK) approvals with identity verification (NIK/face) and electronic document output (e-TBPKP) and document delivery options. Second, other online applications, such as marketplaces/modern retail ecosystems and digital wallets that facilitate PKB payments based on payment codes/virtual accounts, which in practice still require validation at the counter. And the third is the Night Drivethru service, an afternoon-evening service (4:00 p.m. to 7:30 p.m. WIB) at the Sleman Regency KPPD that allows taxpayers to pay without getting out of their vehicles through a simplified process. These three types of services will be the subject of this study. This study analyzes the impact of these three payment services on Motor Vehicle Tax (PKB) revenue at the Sleman Regency Tax Office. The approach used is quantitative with multiple linear regression, preceded by descriptive statistics and classical assumption tests; all processing is done using IBM SPSS Statistics. The simultaneous test results show a significant model (F = 14.239; df = 3.36; p < 0.001) with adequate explanatory power (Adjusted R² = 0.505). Partially, Night Drivethru has a positive and significant effect on acceptance (B = 6,163,346; t = 4.415; p = 0.000), while Other Online Applications and SIGNAL Applications are not significant. These findings indicate that the ease of access to services outside working hours, as facilitated by Night Drivethru, is the most consistent driver of revenue, while digital services require further optimization so that their contribution to revenue becomes more apparent.